Analisis Tingkat Kesulitan Keuangan Perusahaan Makanan dan Minuman Akibat Pandemi Covid-19 - Prihastiwi, Diah Agustina; Nurjannah, A'innisa (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
Since the development of the Corona virus, which was first discovered towards the end of 2019 in Wuhan, Hubei Region, China, it has spread throughout the world because of its fast-spreading contagion. All the affected countries have adopted different strategies to reduce the rate of transmission of this infection, in particular small to large scope social restrictions. The implementation of these approaches in the long term will have a very real impact around the world, one of which is the decline in global financial movements, considering Indonesia. In this study, financial ratios were calculated for all data using financial ratios in the Modified Altman Z-Score model, Grover Score, Zmijewski. The results of the Altman Z-Score Altered model analysis on food and beverage companies during the Coronavirus pandemic, precisely in the 2020 quarter, food and beverage companies are expected to experience financial distress as many as 4 companies. The results of the calculation based on the analysis of the Grover Score model for food and beverage companies during the Coronavirus pandemic, to be precise, per quarter of 2020, the F&B companies that are expected to experience financial distress are 3 companies. The results of calculations based on the Zmijewski model for food and beverage companies during the Coronavirus pandemic, to be precise, per quarter of 2020, food and beverage companies that are expected to experience financial distress are 2 companies.